Vietnam War - Wellington, Jo; Garner, Simon; Classroom Video (Australia : Classroom Video, 2009)
This program examines Australia's involvement in the Vietnam War. A fascinating range of opinions and reflections are presented by those who were involved in and close to the action in the late 1960s and early 1970s and those who have spent years studying the impact of Australi's involvement in this controversial war
Title from container
Executive producer, Simon Garner
DVD Format
Keywords: Vietnam War, 1961-1975